Corporate governance and cash holdings : an empirical investigation of Australian companies. - Cheng, Sai Him. (2008)
This study investigates the relationship between corporate cash holdings in Australian listed companies and various corporate governance factors such as CEO-chairman duality, proportion of outside directors, board tenure and director education.